Efektivitas Ekstrak Cacabean (Ludwigia hyssopifolia G. Don Exell) pada Perkecambahan Biji dan Pertumbuhan Gulma Bobontengan (Leptochloa chinensis L. Nees) - Hidayat Pujisiswanto; Putri Rahmadani; Eko Pramono Pramono; Dad R. J. Sembodo (Jurnal Penelitian Pertanian Terapan, 2024)
The presence of bobontengan weed (Leptochloa chinensis) in rice fields is considered to be detrimental and need to be controlled. Compounds secondary metabolites plant can be used as herbicides for weed control. Cacabean (Ludwigia hyssopifolia) is one of the plants that contain secondary metabolites compounds. This study aimed to determine the potency of the extract of each part of cacabean plant and the level of concentration in germination and growth of bobontengan. The research was carried out from February to March 2023, in the Integrated Field Greenhouse, Faculty of Agriculture, University of Lampung. The research design used a Randomized Block Experiment Design (RAK). The treatment consisted of two factors with four groups. The first factor was the source of cacabean extract: leaves, stems and roots, while the second factor was the concentration of cacabean extract which consisted of 4 levels: 0, 5, 10 and 15%. The homogeneity of variance was tested by Bartlett's test and the additiveness of the data was tested by Tukey's test. If the assumptions are met, the data is analyzed by analysis of variance and differences in treatment mean values followed by the Least Significant Difference (LSD) test at the 5% level. The results showed that extracts of leaves, stems and roots of cacabean at concentrations of 5, 10 and 15% effectively suppressed seed germination and bobontengan weed growth. L.hyssopifolia leaf extract was most effective in suppressing germination, shoot height growth, and dry weight of bobontengan weed. Cacabean leaves and stem extracts were most effective in suppressing the percentage of germination, shoot height growth, and the total dry weight of bobontengan. Concentration of 15% of Cacabean extract was most effective in suppressing the growth of shoot height of 2 MSA, root length, and dry weight of bobontengan, while the concentration of 10-15% was most effective in suppressing the percentage of germination and shoot height of 4 MSA. Sources of cacabean leaves, stem and root extracts were influenced by the level of extract concentration in suppressing seed germination and crown height.